IMPROVING THE MANAGEMENT MECHANISMS OF THE REPUBLIC OF UZBEKISTAN’S HEALTH RESORT COMPLEX IN THE CONTEXT OF MARKET TRANSITIONS (International scientific-electronic journal “Pioneering studies and theories”, 2026)
This article focuses on improving the management mechanism for the health resort complex of the Republic of Uzbekistan, which is undergoing rapid development and transformation in today’s market conditions. Based on an analysis of statistical data and regulatory documents, an assessment of the current management mechanism was conducted, which revealed systemic shortcomings in management, fragmentation of administrative functions, and a lack of coordination among stakeholders. Based on a classification of theoretical approaches found in the scientific literature and international experience in managing health tourism, a partially decentralized management system is proposed and justified. The proposed system includes vertical coordination through the Department of Tourism Development and horizontal integration of health resort organizations through an industry association. Implementation of this proposal will ensure a balance between state regulation and the market autonomy of market participants, create conditions for meeting the social needs of society and the financial and economic interests of owners, and thereby ensure the sustainable development of the health resort complex of the Republic of Uzbekistan.